Combined effect in coherent bremsstrahlung of channeled electrons; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 355 : Channeling 2014: Charged & Neutral Particles Channeling Phenomena - Kunashenko Yu. P. Yuriy Petrovich (2015, 2015)
Title screen